2007
DOI: 10.1152/ajpheart.00194.2007
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of dietary α-linolenic acid or decosahexaenoic acid on incorporation of decosahexaenoic acid in membranes and its influence on rat heart in vivo

Abstract: The present study was designed to evaluate whether long-term intake of dietary alpha-linolenic acid (ALA), supplied as whole grain-extruded linseed, can increase endogenous production of n-3 long-chain polyunsaturated fatty acids (FAs) in healthy adult rats and influence the heart rate (HR) and adrenergic response in the same way as docosahexaenoic acid (DHA)-rich diets. DHA enrichment was evaluated using FA analysis of tissue phospholipids after 8, 16, 24, and 32 wk of feeding in male Wistar rats randomly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 71 publications
4
28
0
Order By: Relevance
“…Dietary a-LNA has been investigated with regard to prevention of cardiovascular disease (58)(59)(60). Dietary a-LNA can reduce cardiac arrhythmias and heart rate in rats, although less effectively than dietary EPA or DHA (58,61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary a-LNA has been investigated with regard to prevention of cardiovascular disease (58)(59)(60). Dietary a-LNA can reduce cardiac arrhythmias and heart rate in rats, although less effectively than dietary EPA or DHA (58,61).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary a-LNA can reduce cardiac arrhythmias and heart rate in rats, although less effectively than dietary EPA or DHA (58,61). We do not know the rate of DHA consumption by the heart, but now know that liver conversion of dietary a-LNA to DHA can maintain the heart DHA concentration in the absence of dietary DHA (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work revealed that male Wistar rats fed PUFA-enriched diets had stable myocardial fatty acid compositions after 2 months of treatment. [12] A dietary treatment duration of 12 weeks was used in an effort to produce LVH while limiting the development of comorbidities. Food intake and body weights were measured twice weekly.…”
Section: Methodsmentioning
confidence: 99%
“…Premenopausal women exhibit a better efficiency for the conversion of ALA to EPA than those found in postmenopausal women and in men. In rats, maximum incorporation of less than 1% ALA was shown to accumulate in cardiac PL within 8 weeks of a 32-week feeding study with 15.8 g of ALA/kg diet [67].…”
Section: Essential Pufa: Structure and Biochemistrymentioning
confidence: 98%